Anti-tau single domain antibodies clear pathological tau and attenuate its toxicity and related functional defects. - Nair, S.; Jiang, Y.; Marchal, I.S.; Chernobelsky, E.; Huang, H.W.; Suh, S.; Pan, R.; Kong, X.P.; Ryoo, H.D.; Sigurdsson, E.M. (Cell death & disease, 2024)
Tauopathies are a group of neurodegenerative diseases characterized by the presence of tau inclusions. We have developed over fifty anti-tau single-domain antibodies (sdAbs) derived from phage display libraries of a llama immunized with recombinant and pathological tau immunogens. We examined the therapeutic potential of four of these sdAbs in a Drosophila tauopathy model following their transgenic expression either in all neurons or neuronal subtypes. Three of these sdAbs showed therapeutic potential in various assays, effectively clearing pathological tau and attenuating or preventing tau-induced phenotypes that typically manifest as defects in neuronal axonal transport, neurodegeneration, functional impairments, and shortened lifespan. Of these three, one sdAb was superior in every assay, which may at least in part be attributed to its tau-binding epitope. These findings support its development as a gene therapy for tauopathies.